Learning Difficulties with Finite Geometries and Remedial Teaching (Surkhet Journal, 2014)
Students‌ face‌ many‌ difficulties‌ in‌ learning‌ and‌ studying‌ finite‌ geometries.‌ Geometry‌ is‌considered‌ as‌ a‌ hard subject from lower levels. In lower levels, even upto higher secondary level, students are taught mainly the Euclidian geometry. In B. Ed level, it is necessary to introduce them with different types of geometries‌ such‌ as‌ finite‌ geometries,‌ Euclidian,‌ non- Euclidian,‌ projective‌ geometry,‌ topology‌ etc.‌ The‌ aim‌ of‌ this‌ research‌ is‌ to‌ find‌ the‌ reasons‌ and‌ facts‌ which‌ make‌ finite‌ geometries‌ hard‌ to‌ understand.‌There‌ are‌ many‌ types‌ of‌ problem that‌ create‌ these‌ dificulties.‌‌ One‌ of‌ the‌ important‌ problems‌ is‌ that‌ most of the students have negative attitude towards geometry that it is a hard subject. Most of them confuse‌ finite‌ geometries‌ with‌ the‌ Euclidian‌ geometry.‌ Some‌ of‌ them‌ have‌ wrong‌ concept that‌ Euclidian‌ geometry is only the geometry that represents the real universe. The problem is on the foundation of the geometry. The little knowledge and understanding about what is geometry? What is an axiomatic system?‌ make‌ serious‌ learning‌ dificulties‌ in‌ finite‌ geometries.